Solving Problems through Engineering Design: An Exploratory Study with Pre-Service Teachers - Isabel Vale; Ana Barbosa; Ana Peixoto; Fátima Fernandes (MDPI AG, 2022)
A possible pathway to achieve disciplinary integration is through the use of the Engineering Design (ED) process, starting with problems in a real context that enable the mobilization of concepts from various disciplinary areas. The study reported in this paper aims to analyze the performance underlying the use of the ED process in solving authentic problems in a STEAM perspective, with future teachers of elementary education. We adopted a qualitative and interpretative methodology, with an exploratory design, where data were collected through participant observation, documents, artefacts and photographic records. The results are discussed, taking into account previous research and the data collected throughout the classes, where future teachers solved a problem task and created an artefact and a poster. Preliminary results show that the participants valued the experience and were actively engaged, showing persistence and motivation in solving the problem in a collaborative way, through the different steps of the ED cycle. This approach constituted an opportunity to favor the establishment of connections between different areas, such as mathematics, sciences or arts, detecting the possibility of integrating previously learned concepts. Difficulties were evidenced in the identification of some underlying mathematical and physical sciences concepts, particularly in the mobilization of an adequate scientific language while arguing and making decisions, or in accurately justifying the need to improve the designed plan.